A comparative analysis of different automated von Willebrand factor glycoprotein Ib-binding activity assays in well typed von Willebrand disease patients - Vangenechten, I; Mayger, K; Smejkal, P; Zapletal, O; Michiels, J J; Moore, G W; Gadisseur, A (Journal of thrombosis and haemostasis, 2018)
UNLABELLED: Essentials Von Willebrand ristocetin cofactor activity (VWF:RCo) is not a completely reliable assay. Three automated VWF activity assays were compared within a von Willebrand disease (VWD) cohort. Raw values for all three assays were virtually the same. An overall problem within type 2A/IIE VWD using VWF:GPIb-binding activity/VWF:Ag was observed. SUMMARY: Background von Willebrand disease (VWD) is an inherited bleeding disorder caused by quantitative (type 1 and 3) or qualitative (type 2) von Willebrand factor (VWF) defect. VWD diagnosis and classification require numerous laboratory tests. VWF: glycoprotein Ib (GPIb)-binding activity assays are used to distinguish type 1 from type 2 VWD. Objectives Three different automated VWF:GPIb-binding activity assays were compared. Patients and methods BC-VWF:RCo (Siemens Healthcare Diagnostics), HemosIL® VWF:RCo (Instrumentation Laboratory) and INNOVANCE® VWF:Ac (Siemens Healthcare Diagnostics) were performed in a well typed VWD cohort (n = 142). Results Based on the three most used VWD parameters (FVIII:C, VWF:Ag and VWF:GPIb-binding activity) and using a cut-off of <0.70 for type 2 VWD revealed sensitivity and specificity of, respectively, 92% and 72.4% for VWF:RCo/VWF:Ag, 84% and 89.7% for VWF:GPIbR/VWF:Ag, and 92% and 85.1% for VWF:GPIbM/VWF:Ag, whereas a lowered cut-off of < 0.60 resulted in reduced sensitivity with increased specificity for all assays. Conclusion VWD classification based on FVIII:C, VWF:Ag and VWF:GPIb-binding activity revealed an overall problem with normal VWF:GPIb-binding activity/VWF:Ag within type 2, especially type 2A/IIE. Although all assays were practically identical, BC-VWF:RCo had higher %CV compared with both new assays but comparable lower limit of quantification (LLOQ) ~4 IU dL-1 . No clear improved distinction between type 1 and 2 VWD with new assays was seen. BC-VWF: RCo and HemosIL® are ristocetin dependent, whereas INNOVANCE® does not rely upon ristocetin and is not influenced by VWF polymorphisms increasing VWF:GPIb-binding activity levels. INNOVANCE® seems to be the best choice as a first-line VWF:GPIb-binding activity assay, providing the best balance between sensitivity and specificity for type 2 VWD.
Keywords: von Willebrandův faktor; Equipment Design; subtypes; classification; Von Willebrand disease; biologické markery; laboratorní automatizace; Hematologic Tests; Biomarkers; Belgie; průřezové studie; Predictive Value of Tests; von Willebrandova nemoc; vazba proteinů; Reproducibility of Results; prediktivní hodnota testů; von Willebrand Diseases; lidé; Belgium; trombocytový glykoproteinový komplex Ib-IX; ristocetin cofactor; reprodukovatelnost výsledků; Cross-Sectional Studies; Czech Republic; von Willebrand factor; hematologické testy; Česká republika; Platelet Glycoprotein GPIb-IX Complex; von Willebrand Factor; Automation, Laboratory; design vybavení; Protein Binding; Humans